Design of two Low DC-Power High-Efficiency D-Band Power Amplifiers in 22 nm FDSOI - Engelmann, Andre; Hetterle, Philip; Probst, Florian; Weigel, Robert; Dietz, Marco (17th European Microwave Integrated Circuits Conference (EuMIC), 2022)
This paper presents two low DC-power D-band power amplifiers (PAs) integrated into a 22nm fully-depleted silicon-on-insulator (FDSOI) technology. Both amplifiers use the capacitive neutralization technique for gain-boosting and stability enhancement. The design procedure for transformer-based (TB) and line-based (LB) matching networks and the advantages and disadvantages of both architectures are discussed. The PA implementation focuses on low DC-power consumption, high efficiency, and compact device realization. The fabricated TBand LB-PA show high maximum power-added-efficiency (PAE) of 9 and 8% consuming 46 and 52mW respectively at a supply voltage of only 0.8V. The saturated output powers Psat reach 6.8dBm and 6.5dBm while achieving small-signal gains of 24.2 and 23.4 dB with 3-dB-bandwidths of 23 and 26 GHz.<br
Keywords: Power amplifier (PA); D-Band; millimeter-wave; FDSOI; CMOS; phase-modulated continuous-wave (PMCW) radar